PENGEMBANGAN MEDIA COUNTING BOX PADA PEMBELAJARAN MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN KELAS 1 SEKOLAH DASAR - Ibrohim, M.; Sofwan, Muhammad; Budiono, Hendra (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The aim of this research is to find out the process of developing media, as well as the level of validity and practicality of counting box media. This research uses research and development (RD) methods with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. Quantitative data was obtained from material and media validation questionnaires as well as teacher and student responses. Qualitative data consists of input from material and media validators regarding the products being developed. The research was conducted in February 2024 in Class I SDN 103/II Tanjung Agung. The material expert validation results showed a percentage score of 87.5% in the very valid category, while the media expert validation results showed a percentage score of 92.5% in the very valid category. The teacher's response shows a percentage score of 95% in the very practical category, and the student response shows a percentage score of 95.60% in the very practical category. Therefore, based on the findings of this research, it can be concluded that the counting box for teaching addition and subtraction material in first grade elementary schools is very valid and practical. The results also show that the counting box is suitable for use